Detection of Atrial Fibrillation after Ischemic Stroke with an Insertable Cardiac Monitor: A Systematic Review and Individual Patient Data Meta-Analysis of Randomized Clinical Trials - Zi Yi Wong (S. Karger AG, 2023)
10.1159/000533265